An Unusual Complication of Intramedullary Pin Migration during Total Knee Arthroplasty – A Case Report - Londhe, Sanjay Bhalchandra; Shah, Ravi Vinod; Banka, Paras (Revista Brasileira de Ortopedia, 2021)
Total knee arthroplasty (TKA) is one of the most effective operations to relieve pain and improve function in the end stage of osteoarthritis (when bone on bone contact occurs). The intraoperative complications of TKA include fracture, tendon or ligament injury, and nerve or vascular complications. We herein describe an unusual complication of intramedullary pin migration within the femoral canal during TKA. A 72-year-old male patient underwent TKA with a posterior stabilization system with sacrifice of the posterior cruciate ligament. The distal femur was sectioned and balance was checked in extension. Then to make anterior, posterior, chamfer and notch cuts, the five-in-one anteroposterior (AP) cutting block was placed on the distal femur and the cuts were initiated. As there was a medial overhang of the cutting block, it was shifted laterally. While doing so, the pins had to be shifted too, and one of them was inadvertently hammered into the previously-created medullary canal opening of the femur. As usual orthopedic instruments, like the long straight artery forceps and pituitary rongeurs, failed to remove the migrated pin, an extralong laparoscopic grasper was used under fluoroscopy control to locate, grasp, and remove the migrated pin.
Keywords: arthroplasty, replacement, knee; bone nails; intraoperative complications; orthopedic procedures